(untitled) (Heritage, 2025)
The subject of this paper is the military lexicon of the Serbian language recorded in the Kragujevac edition of Novina srpskih, which we view as a kind of terminological subsystem within the wider lexical sistem of the Serbian language. The lexical composition of military terms excerpted from the Kragujevac edition of Novina srpskih, in addition to recognizable,purely military terms, also includes words of general use, but also a once-common lexicon standardized in the first phase of the Serbian military terminological system (around the middle of the 19th century), and today outdated terminological lexicon, as well as lexicon of foreign origin that entered in the Serbian language from other languages, and which denote terms that were once relevant in the armies of former foreign administrations on domestic soil. The goal of our work is therefore twofold: 1) lexical-semantic classification of purely military terms on the one hand, and, on the other hand 2) registration and classification of those examples that over time have lost the status of terminological units, as well as those that are part of the general lexical fund, but with a certain meaning they represent part of the military terminology.